Você está na página 1de 8

Mathematical Induction

Theorem 1: Prove that


n(n + 1)
2

1 + 2 + 3 + ... + n =

()

for any integer n 1.


Proof:
STEP 1: For n=1 () is true, since
1=

1(1 + 1)
.
2

STEP 2: Suppose () is true for some n = k 1, that is


1 + 2 + 3 + ... + k =

k(k + 1)
.
2

STEP 3: Prove that () is true for n = k + 1, that is


?

1 + 2 + 3 + . . . + k + (k + 1) =

(k + 1)(k + 2)
.
2

We have
k(k + 1)
1 + 2 + 3 + . . . + k + (k + 1) =
+ (k + 1) = (k + 1)
2
ST.2


k
(k + 1)(k + 2)
+1 =
.
2
2

Theorem 2: Prove that


1 + 3 + 5 + . . . + (2n 1) = n2
for any integer n 1.
Proof:
STEP 1: For n=1 () is true, since 1 = 12 .
STEP 2: Suppose () is true for some n = k 1, that is
1 + 3 + 5 + . . . + (2k 1) = k 2 .
STEP 3: Prove that () is true for n = k + 1, that is
?

1 + 3 + 5 + . . . + (2k 1) + (2k + 1) = (k + 1)2 .


ST.2

We have: 1 + 3 + 5 + . . . + (2k 1) + (2k + 1) = k 2 + (2k + 1) = (k + 1)2 . 

()

Theorem 3: Prove that


n! nn

()

for any integer n 1.


Proof:
STEP 1: For n=1 () is true, since 1! = 11 .
STEP 2: Suppose () is true for some n = k 1, that is k! k k .
?

STEP 3: Prove that () is true for n = k + 1, that is (k + 1)! (k + 1)k+1 . We have


ST.2

(k + 1)! = k! (k + 1) k k (k + 1) < (k + 1)k (k + 1) = (k + 1)k+1 . 

Theorem 4: Prove that


32n 1 div. by 8

()

for any integer n 0.


Proof:
STEP 1: For n=0 () is true, since 30 1 is divisible by 8.
STEP 2: Suppose () is true for some n = k 0, that is 32k 1 is divisible by 8.
STEP 3: Prove that () is true for n = k + 1, that is 32(k+1) 1 is divisible by 8. We have
32(k+1) 1 = 32k+2 1 = 32k 9 1 = 32k (8 + 1) 1 = |32k{z 8} + 3| 2k{z 1} . 
div. by 8
St. 2
div. by 8

PROBLEMS
I. Prove by induction the following identities:
n(n + 1)
.
2

1.

1 + 2 + 3 + ... + n =

2.

1 + 3 + 5 + . . . + (2n 1) = n2 .

3.

12 + 22 + 32 + . . . + n2 =

4.

1 2 + 2 3 + 3 4 + . . . + (n 1)n =

5.

1
1
1
1
n1
+
+
+ ... +
=
.
12 23 34
(n 1)n
n

6.

7.
8 .

n(n + 1)(2n + 1)
.
6
n(n 1)(n + 1)
.
3

1
1
1
1
n
+
+
+ ... +
=
.
13 35 57
(2n 1)(2n + 1)
2n + 1



 

1
1
1
1
1
1
1
1
... 1
= .
2
3
4
n
n

1
1
1
1
+
+
+ ... +
= n 1.
n1+ n
1+ 2
2+ 3
3+ 4
sin

9 . sin + sin 2 + sin 3 + . . . + sin n =

(n + 1)
n
sin
2
2
.

sin
2

II. Prove by induction the following inequalities:


1.

2n > n for any integer n 1.

2.

n! > n2 for any integer n 4.

3.

2n < n! for any integer n 4.

4.

3n < n! for any integer n 7.

5.

3n 2n + 1 for any integer n 1.

6.

n! nn for any integer n 1.

7.

2n+2 2n + 5 for any integer n 1.

8 .

(2n)! < 22n (n!)2 for any integer n 1.

9 .

(n + 1)n < nn+1 for any integer n 3.



n
an1 + an2
a1 + a2
for any positive numbers a1 , a2 and for any integer n 1.

2
2

10 .
11 .

1
1
1
1
+ 2 + 2 + . . . + 2 < 2 for any integer n 1.
2
1
2
3
n

III. Prove by induction the following problems:


1.

n3 n is divisible by 3 for any nonnegative integer n.

2.

n5 n is divisible by 5 for any nonnegative integer n.

3.

n3 7n + 3 is divisible by 3 for any nonnegative integer n.

4.

4n 1 is divisible by 3 for any nonnegative integer n.

5.

32n 1 is divisible by 8 for any positive integer n.

6.

7n 2n is divisible by 5 for any nonnegative integer n.

7 .

32n+3 + 40n 27 is divisible by 64 for any nonnegative integer n.

8 .

52n+1 2n+2 + 3n+2 22n+1 is divisible by 19 for any nonnegative integer n.


!n
!n !
1
1
+
5
1

5
9 .

is integer for any nonnegative integer n.


2
2
5

Theorem : Prove that


1 + 2 + 3 + ... + n =
Proof :

n(n + 1)

for any integer n 1.

()

STEP1 : For n = 1 () is true, since


1(1 + 1)
.
1=
2
STEP2 : Suppose () is true for some
n = k 1, that is
k(k + 1)
1 + 2 + 3 + ... + k =
.
2
STEP3 : Prove that () is true for n = k + 1 :
? (k + 1)(k + 2)
.
1 + 2 + 3 + . . . + k + (k + 1) =
2
We have :
1 + 2 + 3 + . . . + k + (k + 1)
ST.2 k(k + 1)
=
+ (k + 1)
2
(k + 1)(k + 2)
=
.
2

Theorem : Prove that


1 + 3 + 5 + . . . + (2n 1) = n2
for any integer n 1.

()

Proof :
STEP1 : For n = 1 () is true, since
1 = 12 .
STEP2 : Suppose () is true for some
n = k 1, that is
1 + 3 + 5 + . . . + (2k 1) = k2.
STEP3 : Prove that () is true for n = k + 1 :
?

1 + 3 + 5 + . . . + (2k 1) + (2k + 1) = (k + 1)2.


We have :
1 + 3 + 5 + . . . + (2k 1) + (2k + 1)
ST.2

= k2 + (2k + 1)
= (k + 1)2. 

Theorem : Prove that


n! nn
for any integer n 1.

()

Proof :
STEP1 : For n = 1 () is true, since
1! = 11.
STEP2 : Suppose () is true for some
n = k 1, that is :
k! kk .
STEP3 : Prove that () is true for n = k + 1
?

(k + 1)! (k + 1)k+1.
We have :
ST.2

(k + 1)! = k! (k + 1) kk (k + 1)
< (k + 1)k (k + 1)
= (k + 1)k+1. 

Theorem : Prove that


32n 1 div. by 8
for any integer n 0.

()

Proof :
STEP1 : For n = 0 () is true, since
30 1 div. by 8.
STEP2 : Suppose () is true for some
n = k 0, that is
32k 1 div. by 8.
STEP3 : Prove that () is true for n = k + 1 :
?
2(k+1)
3
1 div. by 8.

We have :
2k 8 + 32k 1 .
32(k+1) 1 = 32k 9 1 = 3
| {z } | {z }
div. by

St. 2
div. by 8